Assessment of the medical biotechnology industry in Singapore. - Chia, Diana Guan Boon. (2008)
Seeing the industry’s promising future, Singapore has aimed to developed biotechnology as the fourth pillar of the economy (Ministry of Trade, 2000). Thus, this research work assesses the strength, weaknesses and competitive advantage of the Singapore medical biotechnology industry versus Denmark and other Asian nations.